Kualitas Pelayanan Publik Daerah melalui Transparansi Informasi Peraturan Gubernur di Biro Hukum Sekretariat Daerah Provinsi Banten - Nasywa Nathania Sukma; Anti Wulan Agustini (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2026)
Community service is a form of implementation of the Tri Dharma of Higher Education which aims to make a real contribution to society through the application of science and research results. This activity focuses on improving the quality of regional public services through transparency of information on governor's regulations at the Legal Bureau of the Banten Provincial Regional Secretariat. The problem faced by the community is that there is still limited access and understanding of various regional law products, especially governor's regulations related to the implementation of government and public services. The methods used in this activity include the preparation stage, implementation of socialization, delivery of information, and evaluation of activities to the community. The results of the activity show that transparency of legal information is able to increase public understanding of local government policies and encourage community participation in the process of implementing government. In addition, this activity also contributes to increasing public legal awareness and strengthening the relationship between the government and the community. Thus, information transparency is an important factor in realizing good and accountable governance, transparent, effective, efficient, and oriented to the public interest.